Evaluation of the Causes of Defects in Woven Sarongs at PT Ibrahim Bin Manrapi Using the Six Sigma Method - Abdul Kholiq; Rahmat Agus Santoso (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to trigger the causes of defects in woven sarong products at PT Ibrahim Bin Manrapi and provide improvement solutions through the application of the Six Sigma method with the DMAIC (Define, Measure, Analyze, Improve, Control) approach. The main problem faced by the company is the high level of product defects which reaches an average of 4.21% of total production, with the dominant types of defects including sewing defects (46.36%), color defects (24.96%), size defects (16.53%), and torn fabric (12.15%). Data were obtained through in-depth interviews, observations, and documentation in the production department. The measurement results show a Defects Per Million Opportunities (DPMO) value of 42,100 with a sigma level of 3.36, which indicates that production quality is still below Six Sigma standards. Analysis of the causes of defects using the 5M approach (Man, Machine, Method, Material, Measurement) shows that the main factors causing defects come from old ATBM weaving machines, lack of operator accuracy and skills, complicated manual work methods, and the absence of consistent quality control standards at the end of the process. Recommended improvement efforts include machine rejuvenation, workforce training, implementation of standard operating procedures (SOPs), and continuous quality monitoring through the use of control charts. The application of the Six Sigma method has proven effective in helping companies identify problem sources and develop strategies for systematic and sustainable product quality improvement.